The learning curve of laparoscopic inguinal hernia repair: A comparison of three inexperienced surgeons - Göksoy, Beslen; Azamat, İbrahim Fethi; Yılmaz, Gökhan; Sert, Özlem; Onur, Ender (Termedia Publishing House Ltd, 2021)
Introduction: Studies with inexperienced surgeons in terms of the learning curve for laparoscopic totally extraperitoneal (TEP) inguinal hernia repair are limited. Aim: To compare three inexperienced surgeons in terms of the learning curve without supervision. Material and methods: Patients' data, which were from consecutive laparoscopic TEP hernioplasties between December 2017 and February 2020, were analysed retrospectively. The primary outcome was to compare the learning curve of three surgeons (Surgeon A, B, and C) in terms of complications, conversion, and duration of surgery. Secondary outcomes were recurrence rates. Results: A total of 299 patients were included in the study. Conversion and intraoperative complication rates decreased after the first 60 cases (from 10% to 2.5%, p = 0.013 and from 9% to 2.5%, p = 0.027, respectively). The mean operative time reached a plateau of less than 40 min after 51-81 cases (Surgeon A 51, B 71, and C 81 cases). Ageing was a risk factor for intraoperative complications and recurrence (p < 0.001, p = 0.008, respectively), and higher body mass index (BMI) was a risk factor for conversion (p = 0.004). Age = 60 years compared to age < 60 years increased intraoperative complications five-fold and recurrence six-fold (p = 0.001). On the other hand, BMI = 30 kg/m(2) increased the possibility of conversion to open surgery nine-fold (p < 0.001). In addition, a positive correlation was found between the operative time and the BMI and VAS score (p = 0.004, p = 0.015, respectively). Conclusions: In order to reach the plateau in the operative time during the TEP learning curve period, more than 50 cases should be experienced, whereas more than 60 cases are needed for conversion, intraoperative complications, and recurrence.
Keywords: Laparoscopy; Totally Extraperitoneal; Inguinal Hernia; Learning Curve; Transabdominal Preperitoneal